Multistage Security-Constrained HVAC/HVDC Transmission Expansion Planning With a Reduced Search Space - Hernando Dominguez, Andres; Macedo, Leonardo H. [UNESP]; Hernando Escobar, Antonio; Romero, Ruben [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2017)
This paper proposes a new method to solve the multistage security-constrained transmission expansion planning problem, incorporating lines based on high-voltage alternating current (HVAC) and high-voltage direct current (HVDC) alternatives. A novel mixed-integer linear programming model, which incorporates transmission losses using a piecewise linearization, is presented. An efficient method to reduce the search space of the problem is developed to help in the solution process. Garver's 6-bus system and a modified Southern Brazilian system are used to show the precision and efficiency of the proposed approach. The tests are performed for cases with and without HVDC links and transmission losses. The results indicate that better expansion plans can be found by considering HVDC proposals in the expansion process. The promising trend of using HVDC lines in future networks to improve the reliability in the system is demonstrated.
Keywords: HVDC lines; mixed-integer linear programming; multistage transmission expansion planning; power losses; security constraints